2018
DOI: 10.1148/radiol.2018180078
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Discontinuation prior to FDG PET/CT: A Randomized Controlled Study to Compare 24- and 48-hour Bowel Activity

Abstract: Purpose To investigate the relationship of 24- and 48-hour metformin discontinuation to bowel uptake of fluorine 18 fluorodeoxyglucose (FDG) on PET/CT scans. Materials and Methods Patients with diabetes who were treated with metformin and referred for FDG PET/CT were randomized to three equal groups based on duration of metformin discontinuation: 24 hours, 48 hours, and no discontinuation (control group). Two interpreters blinded to the study groups assessed FDG uptake in multiple segments of small and large b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
2
22
2
Order By: Relevance
“…In our study, performed in a European population, we included more patients discontinuing metformin for at least 48 h (n = 25), this contributes evidence to the theory that a metformin discontinuation period of 48 h is insufficient to prevent FDG uptake in all of the colonic segments. Our results contradict the results found in a study by Hamidizadeh et al which showed that a discontinuation period of 48 h lowered the FDG uptake in all of the colonic segments [8]. In our study, we used a different control group in comparison with the studies of Lee et al and Hamidizadeh et al [8,9].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In our study, performed in a European population, we included more patients discontinuing metformin for at least 48 h (n = 25), this contributes evidence to the theory that a metformin discontinuation period of 48 h is insufficient to prevent FDG uptake in all of the colonic segments. Our results contradict the results found in a study by Hamidizadeh et al which showed that a discontinuation period of 48 h lowered the FDG uptake in all of the colonic segments [8]. In our study, we used a different control group in comparison with the studies of Lee et al and Hamidizadeh et al [8,9].…”
Section: Discussioncontrasting
confidence: 98%
“…The Society of Nuclear Medicine and Molecular Imaging (SNMMI) does not specify guidelines for PET procedures made in patients on oral antidiabetics [7]. However, several studies have suggested that metformin should be discontinued prior to the FDG PET scan [2][3][4], and have recommended feasible and optimal discontinuation periods of metformin [4,8,9] to limit the amount of FDG uptake. Even so, the results in these studies are contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective randomized single centre trial comparing the effects of a 24H- and 48H metformin discontinuation, Hamidizadeh and colleagues [ 33 ] provided solid evidence to support a 48H metformin discontinuation prior to FDG PET scan, with limited impact on glycaemia.…”
Section: Withholding Metformin Prior To Fdg Pet/ct (Fig 8 mentioning
confidence: 99%
“…Beyond case examples, we also need data to support the degree to which this protocol improves the sensitivity or the confidence of readers to diagnose FDG-avid abdominopelvic malignancies. case for withholding metformin for 48 hours prior to FDG PET scans (3). A total of 90 study participants with diabetes were randomly separated into three equal cohorts of 30; metformin was discontinued at 24 hours or 48 hours prior to FDG PET/CT scans, and a control cohort of study participants with diabetes continued on metformin.…”
mentioning
confidence: 99%